Communication Skills Development of Musical Lessons for Children up to Three Years - Kušnere, Sandija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper will be made theoretical and empirical research. The aim of the paper – to explore the musical lessons communication skills development for children up to tree years. The theoretical part of the paper will be based on scientific research in Latvian, Russian and European literature. In theory will be studied music lessons and musical diversity component applications to improve the communication skills of children up to three years. The empirical part will be described in musical activities that have been developed based on scientific grounds to improve the communication skills of children up to three years.The research results will be described in the children’s communication skills and the development of musical training process.